2012
DOI: 10.1111/j.1468-036x.2011.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Time‐Varying Liquidity Trading, Private Information and Insider Trading

Abstract: This paper investigates the insider trading before scheduled versus unscheduled corporate announcements to explore how corporate insiders utilise their private information in response to the time-varying liquidity trading. Using a comprehensive insider trading database, we show that: (1) the insider's propensity to trade increases in the amount of liquidity trading before both the scheduled and unscheduled announcements; (2) insiders buy (sell) more before positive (negative) announcements; and (3) insider pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
2
4
0
1
Order By: Relevance
“…Similarly, Baty (2008) found that directors' purchases demonstrated a positive average abnormal return for most of the event window tested. Our results support all these views, and those of Korczak, Korczak and Lasfer (2010) and Lei and Wang (2012) and suggest that directors have the ability to tactically time the market, and that investors who imitate directors' purchases can obtain abnormal returns (Bodie, Kane & Marcus, 2011).…”
Section: Buy Portfoliosupporting
confidence: 77%
“…Similarly, Baty (2008) found that directors' purchases demonstrated a positive average abnormal return for most of the event window tested. Our results support all these views, and those of Korczak, Korczak and Lasfer (2010) and Lei and Wang (2012) and suggest that directors have the ability to tactically time the market, and that investors who imitate directors' purchases can obtain abnormal returns (Bodie, Kane & Marcus, 2011).…”
Section: Buy Portfoliosupporting
confidence: 77%
“…My study contributes to the literature on pre‐announcement trading behaviours, which tends to focus on boosted informed trading, trades by insiders (Meulbroek, ; Ravina and Sapienza, ; Cohen et al ., ) and trades beyond insiders (Aktas et al ., ; Christophe et al ., ; Kaniel et al ., ; Baruch et al ., ). Few studies have addressed the reduced response in trading behaviours, and they are mainly concentrated on insider silence (Marin and Olivier, ; Lei and Wang, ; Akbas, ), and investor inattention (Loh, ; Louis and Sun, ; Michaely et al ., ). Discussions on the behaviour of liquidity traders are limited, and, in most cases, they are being treated as noise traders.…”
Section: Introductionmentioning
confidence: 99%
“…() focus on dividend announcements and group them into anticipated and unanticipated dividend announcements but do not verify whether an anticipated dividend announcement is informational or not (as an announcement with an unchanged dividend may contain no incremental information) which may affect informed traders’ trading interests. Chae () and Lei and Wang () classify corporate announcements into scheduled and unscheduled events, but do not consider the various predictability of unscheduled events, as some are easier to predict than others. My study contributes to optimising the researchers’ classification method by distinguishing the events which can be anticipated from the unscheduled group, as liquidity traders can continue to choose to wait for the news if the news is predictable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insiders could easily trade and act with attempt to infl uence market prices. Lei and Wang (2014) investigate the insider trading in the US stock market between scheduled versus unscheduled corporate announcements to explore how corporate insiders use their private information. They fi nd that insider buy (sell) more before positive (negative) announcements and their purchases are more profi table before unscheduled announcements than before scheduled ones.…”
Section: Introductionmentioning
confidence: 99%